Good Manufacturing Practice (GMP) in Tofu MSMEs in North Aceh - Cut Ita Erliana; Iskandar Hasanuddin; Yuwaldi Away; Raja Ariffin Raja Ghazilla (Universitas Mercu Buana, 2023)
This study examined tofu MSMEs in Lhokseumawe City and the North Aceh District. Observations indicate discrepancies between tofu production and the GMP requirements for Good Manufacturing Practices. The amount that the tofu sector has adopted appropriate food production procedures by the Regulation of the Ministry of Sector of the Republic of Indonesia Number 75/M-IND/PER/7/2010 is determined using a GMP approach. This research is anticipated to improve the product safety of the tofu industry and provide recommendations for improvement. In this study, data collection techniques included candid interviews related to the GMP aspect questionnaire consisting of 11 inspection aspects, direct field observation of 21 MSMEs by marking the location conditions, production equipment, and materials used, and following the processing process, followed by a search for deviations from GMP aspects and comparison with the literature review, documentation of the necessary data related to GMP assessment, and a search for relevant literature. According to the evaluation, 12 MSMEs with a value range of 41% to 60% fell into the category of not meeting the requirements. The second criterion is extremely inadequate, ranging from 21% to 40% for five MSMEs. Additionally, the criteria for sufficient completion with a range of values between 61% and 80% for up to 4 MSMEs led to an evaluation of 11 GMP aspects in 21 MSMEs. Know on the location aspect with a percentage of 71% in the sufficient category, building aspects with a percentage of 11% in the critical category, aspects of sanitation with a percentage of 40% in the category of very less fulfilling, aspects of machinery and equipment with a percentage of 80% in the category of sufficiently fulfilling, aspects of materials with a percentage of 100% in the category of fulfilling, and aspects of supervision with a percentage of 40% in the category of fulfilling.